PENGARUH MOTIVASI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. VENUS SARANA SUKSES TANGERANG SELATAN - Eni Parwati; Faisal Romdonih (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of motivation and work training on employee performance at CV. Venus Means Success partially and simultaneously. The method used is a quantitative method with a causal associative approach. The population in this study were CV employees. Venus Sarana Sukses with a sample of 60 respondents, data collection technique using a questionnaire. Data analysis uses validity tests, reliability tests, classical assumption tests, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing using SPSS version 25. The results of this research are that motivation partially has a positive and significant effect on employee performance with the regression equation . Y=13.429 + 0.694X1, correlation coefficient of 0.759, meaning the two variables have a strong relationship with a coefficient of determination of 57.6%. and hypothesis testing obtained tcount > ttable or (8.883 > 2.002) then H01 is rejected and Ha1 is accepted. Royal Training partially has a positive and significant effect on employee performance with the regression equation Y=7129 + 0.838X2, a correlation coefficient of 0.873, meaning that the two variables have a very strong relationship with a coefficient of determination of 76.2%. and hypothesis testing obtained tcount > ttable or (13.162 > 2.002) then H02 is rejected and Ha2 is accepted. Motivation and Royal Training simultaneously have a positive and significant effect on employee performance with the multiple linear regression equation Y= 6.936 + 0.053X1 + 0.791X2. The correlation coefficient value obtained is 0.873, meaning that the independent variable and the dependent variable have a strong relationship with a coefficient of determination of 76.3% while the remaining 23.7% is influenced by workload, work environment and work discipline. Hypothesis testing obtained a value of Fcount > Ftable or (91.503 > 3.16), thus Ho3 was rejected and Ha3 was accepted.